1986
DOI: 10.1111/j.1365-3024.1986.tb01038.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of pulmonary cellular reactions in the resistance of vaccinated mice to Schistosoma mansoni

Abstract: A histopathological and ultrastructural study was made of schistosomula and associated inflammatory reactions in the lungs of normal mice, and mice previously vaccinated with irradiated cercariae. In normal mice at day 7 post-infection all schistosomula were located in blood vessels. From day 11 onwards an increasing proportion of schistosomula were intra-alveolar (80% from day 20). No cellular reactions were evident around intravascular parasites in normal mice but at later sampling times large compact foci w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
1

Year Published

1988
1988
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 40 publications
0
64
1
Order By: Relevance
“…To evaluate the relevance of these in vitro observations to immunity in vivo, we examined morphologic changes in the lungs of mice vaccinated with radiation-attenuated parasites after challenge infection. In addition to the presence of inflammatory foci in the lung parenchyma previously described (5,15), remarkable endarteritis and periarteritis were observed, with mononuclear cell and eosinophil infiltration.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…To evaluate the relevance of these in vitro observations to immunity in vivo, we examined morphologic changes in the lungs of mice vaccinated with radiation-attenuated parasites after challenge infection. In addition to the presence of inflammatory foci in the lung parenchyma previously described (5,15), remarkable endarteritis and periarteritis were observed, with mononuclear cell and eosinophil infiltration.…”
Section: Resultsmentioning
confidence: 90%
“…On day 21 after infection, most of the larvae detectable in the lungs of vaccinated mice are located within blood vessels, although -25% are found within alveolar spaces. About half of the identifiable larvae in either site are surrounded by moderate to intense inflammatory reactions consisting mostly of mononuclear cells (15,16).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the mechanism of antibody-mediated attrition, mice vaccinated with repeat (2 or 3) exposures and in which antibody is believed to play a key role, show essentially similar mononuclear cellrich foci around challenge LS in the lung Kassim et al 1992) as have been described for singly vaccinated mice (Crabtree and Wilson, 1986). Again the larvae appear undamaged and a proportion of them occur within alveoli, in which case they induce marked inflammatory responses (Kassim et al 1992).…”
Section: Antibody-mediated Immunitymentioning
confidence: 91%
“…Cells accumulate within the blood vessel and between the vascular endothelium and the alveolar epithelium resulting, it is suggested, in the intravascular migration of the larvae being impeded. Certainly, with time, an increasing proportion of larvae occur within alveoli where they induce even more pronounced foci (Crabtree and Wilson, 1986). Although Von Lichtenberg et al (1985) described damaged LS in vaccinated mice, Crabtree and Wilson (1986) found no evidence of parasite damage and this led to the notion that LS may not be killed within the lung but rather diverted from their intravascular migration into the alveoli and subsequently lost via the trachea and eventually the GI tract.…”
Section: A)mentioning
confidence: 99%
See 1 more Smart Citation